Regulatory Disharmony In Mining Downstream Policies: Ensuring Investment Certainty And Environmental Protection In Indonesia - Arya Elang Anom; Zulfikri Toguan; Azbi Arief Habibi (International Journal of Health Engineering and Technology, 2026)
Indonesia's mining downstream (hilirisasi) policy, grounded in Law Number 3 of 2020 on Mineral and Coal Mining and Law Number 11 of 2020 on Job Creation, faces serious challenges stemming from regulatory disharmony that threatens investment certainty and weakens environmental protection. This study aims to analyze three main dimensions of such disharmony: first, the normative conflict between centralization of mining authority and regional government authority under Law No. 23 of 2014; second, the "green economy" paradox between promoting nickel downstream for the global electric vehicle supply chain and tangible ecological damage on the ground; third, the fragmentation of environmental responsibility following the establishment of Danantara as a Sovereign Wealth Fund. This research employs a normative juridical method with statutory, conceptual, and comparative approaches. The findings indicate that regulatory disharmony creates normative vacuums in local-level environmental oversight, generates risks of greenwashing in Indonesia's green economic diplomacy, and obscures the locus of responsibility between parent companies and operating subsidiaries for environmental compliance. This study recommends the establishment of an integrative legal instrument mandating ESG (Environmental, Social, and Governance) internalization as a precondition for business certainty, supported by multi-level oversight mechanisms that preserve meaningful regional roles.